COVID-19 : PENERAPAN PEMBELAJARAN DARING DI PERGURUAN TINGGI - Tuti Marjan Fuadi; Riki Musriandi; Linda Suryani (Jurnal Dedikasi Pendidikan, 2020)
This study aims to determine the various types of applications used in the online learning process in University during the emergency period to prevent the spread of Covid 19. This research uses a literature study of several articles that discuss online learning in university visiting various pages or articles from the World Wide Web. Presentation of the results is done narratively. The result of the study show there are 9 types of applications that are often used in the online learning process. The 9 types of applications that are often used include; (1) zoom, (2) google classroom, (3) Whatapp group, (4) google meet, (5) skype, (6) Webex, (7) email, (8) Edmodo dan (9) camstudio.